The Emerging Physician-Scientist Workforce: Demographic, Experiential, and Attitudinal Predictors of MD-PhD Program Enrollment - Jeffe, Donna B. (2014)
PURPOSE: MD-PhD scientists are a very successful, but small and fairly homogenous group of biomedical researchers. The authors conducted a retrospective cohort study to identify predictors of MD-PhD program enrollment to inform the development of evidence-based strategies to increase the size and diversity of the biomedical research workforce. METHOD: Using de-identified data from all 2001–2006 Pre-Medical College Admission Test Questionnaire (PMQ) respondents, the authors developed multivariate logistic regression models to identify the demographic, experiential, and attitudinal variables associated with MD-PhD program enrollment at matriculation compared with all other MD program enrollment at matriculation and with not enrolling in medical school by August 2012. RESULTS: Of 207,436 PMQ respondents with complete data for all variables of interest, 2,575 (1.2%) were MD-PhD program enrollees, 80,856 (39.0%) were other MD program enrollees, and 124,005 (59.8%) were non-medical school matriculants. Respondents who were black (vs. white), high school and college laboratory research apprenticeship participants, and highly endorsed the importance of research/finding cures as reasons to study medicine were more likely to be MD-PhD program enrollees, whereas respondents who highly endorsed the status of medicine as a reason to study medicine were less likely to be MD-PhD program enrollees than either other MD program enrollees or non-medical school matriculants. CONCLUSIONS: MD-PhD program directors appear to be successful in enrolling students whose attitudes and interests align with MD-PhD program goals. Continued efforts are needed to promote MD-PhD workforce diversity and the value of both high school and college research apprenticeships for students considering careers as physician-scientists.